Influence of the IMF Cone Angle on Invariant Latitudes of Polar Region Footprints of FACs in the Magnetotail: Cluster Observation. Issue 4 (6th April 2018) - Cheng, Z. W.; Shi, J. K.; Zhang, J. C.; Torkar, K.; Kistler, L. M.; Dunlop, M.; Carr, C.; Rème, H.; Dandouras, I.; Fazakerley, A.
Abstract: The influence of the interplanetary magnetic field (IMF) cone angle θ (the angle between the IMF direction and the Sun‐Earth line) on the invariant latitudes of the footprints of the field‐aligned currents (FACs) in the magnetotail has been investigated. We performed a statistical study of 542 FAC cases observed by the four Cluster spacecraft in the Northern Hemisphere. The results show that there are almost no FACs when the IMF cone angle is less than 10°, and there are indications of the FACs in the plasma sheet boundary layers being weak under the radial IMF conditions. The footprints of the large FAC (>10 nA/m 2 ) cases are within invariant latitudes <71° and mainly within IMF cone angles θ > 60°, which implies that the footprints of the large FACs mainly expand equatorward with large IMF cone angle. The equatorward boundary of the FAC footprints in the polar region decreases with increasing IMF cone angle (and has a better correlation for northward IMF), which shows that the IMF cone angle plays an important controlling role in FAC distributions in the magnetosphere‐ionosphere coupling system. There is almost no correlation between the poleward boundary and the IMF cone angle for both northward and southward IMF. This is because the poleward boundary movement is limited by an enhanced lobe magnetic flux. This is the first time a correlation between FAC footprints in the polar region and IMF cone angles has been determined. Key Points: Only the equatorward boundary of polar region footprints of FACs in the magnetotail lowers with increasing IMF cone angle The footprints of FACs (with large density) are located at ILAT < 71° and mainly correspond to large IMF cone angles (theta > 60°) The relationship between polar region footprints of FACs in the PSBL and the IMF cone angle is determined for the first time